Dormancy breaking in seeds of different accessions of Luffa cylindrica Roemer - Oliveira, Francisca Sonally; Silveira, Lindomar Maria da; Torres, Salvador Barros; Costa, Ferdinando Monteiro Carvalho Dias da; Nunes, Maclayver Christiano Caetano; Silva Neto, José Sisenando de Senna e (Comunicata Scientiae, 2019)
Luffa cylindrica Roemer is abundant in countries of Asia, Central America and South America. Dormancy in luffa seeds is caused by the impermeability of the coat, which may be a major obstacle in the commercial production of seedlings for the cultivation of this species. Thus, this study aimed to evaluate different methods to break dormancy in different accessions of luffa. The experimental design was completely randomized, in a 6 (accessions) x 5 (dormancy breaking treatments) factorial arrangement, with four replicates. Seeds were planted on expanded polystyrene trays, containing commercial substrate Plantmax®. The analyzed variables were: emergence percentage; emergence speed index; number of true leaves; plant height; stem diameter; root length; shoot fresh and dry matter, and root dry matter. The first two variables were analyzed in the entire experimental plot and the others only in the evaluated area of the plot. Scarification with sandpaper nº 80 and cut with pruning pliers on the opposite end to the hilum were the methods of dormancy breaking which led to the best results. Due to the variability of the results among the accessions, it was not possible to recommend one method of dormancy breaking for luffa seeds that is generalized for all of them.